Lipoid proteinosis - Sen Sumit; Roy Gautam; Bandopadhyay Debabrata (Wolters Kluwer Medknow Publications, 2006)
Lipoid proteinosis, a rare autosomal recessive disorder, results from the deposition of hyaline material in the skin, mucous membrane and different organs of the body resulting in a multitude of clinical manifestations. Here the case of a 12 year old boy, of non-consanguineous parcentage, with classical beaded papules along the eyelid margin, waxy facial skin and a history of repeated skin infections that left scars over his face and body. Apart from hoarseness of voice he had no other systemic manifestation. No other member in his family was involved.